The Reflection of the Epos aoKitabi-Dada Gorguda in K. Abdullaas Postmodernist Novel aoThe Incomplete Manuscripta (Global Journal of Human-Social Science, 2016)
In the Azerbaijani prose the postmodern interpretation of the epos "Kitabi-Dada Gorgud", is connected with the creative work of the outstanding Azerbaijani scientist, writer, poet, public figure Kamal Abdulla. The writer's creative work connected with this ancient Turkic epos is a result of the longstanding work, including his scientific works. K. Abdulla's creative work which is remarkable for the close connection of the subject motives that logically continue one another, is very complicated. Thus, this scientist-writer's artistic and scientific works is a unique and original phenomenon that has no analog in the Azerbaijani literary-scientific environment. K. Abdulla does not adhere to previous traditions, but there is a pronounced tradition in his creation that is difficult to appreciate. This tradition was created by K. Abdulla himself. Developing the traditions of interpretation of the epos "Kitabi-Dada Gorgud" in his artistic creation, he spreads confusion in the modern Azerbaijani criticism. Thus, since the beginning of the III millennium there has not been such an artistic work which has been written and which has provoked such excited discussions as K. Abdulla's novel "The incomplete manuscript" published in 2004. Actually this novel disturbed the literary and scientific environment.
Keywords: “kitabi-dada gorgud”; novel; k abdulla; “the incomplete manuscript”